Quantitative proteomics using SWATH-MS identifies mechanisms of chloride tolerance in the halophilic acidophile Acidihalobacter prosperus DSM 14174 - Khaleque, H.; Kaksonen, A.; Boxall, N.; Watkin, Elizabeth (Elsevier Masson SAS, 2018)
In this study, the differential protein expression of the acidophilic halophile, Acidihalobacter prosperus DSM 14174 (strain V6) was studied with the aim of understanding its mechanisms of tolerance to high chloride ion stress in the presence of low pH, using Sequential Window Acquisition of all Theoretical Mass Spectra (SWATH-MS). In acidophiles, chloride stress results in both osmotic stress as well as acidification of the cytoplasm due to the ability of chloride to permeate the cell membrane and disrupt the reversed transmembrane potential which normally extrudes protons. The proteomic response of Ac. prosperus DSM 14174 to elevated chloride concentrations included the production of osmotic stress regulators that potentially induced the production of compatibles solutes, of which the most significant increase was in the synthesis of ectoine. Other responses directly related to the increased chloride and acid stress, included the increased synthesis of glutathione, changes in carbon flux, the increased production of amino acids, the decreased production of ribosomal proteins, the efflux of metals and protons, and the increase in proteins involved in DNA repair and membrane biosynthesis. Energy generation through iron oxidation and sulfur oxidation were decreased, and energy was probably obtained from the metabolism of glycogen stores. Overall, these studies have helped to create a model of tolerance to elevated chloride under acidic conditions by Ac. prosperus DSM 14174 that differs from the previous model developed for the type strain, Ac. prosperus DSM 5130T.